International commercial contracts : applicable sources and enforceability - Cordero-Moss, Giuditta (Cambridge University Press, 2014)
"Any practising lawyer and student working with international commercial contracts faces standardised contracts and international arbitration as mechanisms for dispute settlement. Transnational rules may be applicable, but national law is still important. Based on extensive practical experience, this book analyses international contract practice and its interaction with the various applicable sources: which role is played by the contractual regulation, which by national law, which by transnational sources, what is the interaction among these factors, and how does this all apply to contracts that refer disputes to international arbitration?"--